Análise de um programa de reabilitação sobre as mensurações de gibosidade, lordoses, dor e qualidade de vida - Shimizu, Ananda Yumi [UNESP]; Hisamatsu, Thalysi Mayumi [UNESP]; Ladvig, Raissa Puzzi [UNESP]; Veronese, Thiago Pereira [UNESP]; Santos, Fernanda Berno dos [UNESP]; Anadão, Felipe Novaes [UNESP]; Almeida, Nathália Raphaela Mantovani de [UNESP]; Pachioni, Célia Aparecida Stellutti [UNESP]; Fregonesi, Cristina Elena Prado Teles [UNESP]; Ferreira, Dalva Minonroze Albuquerque [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The study examined the influence of a group exercise program in subjects with idiopathic scoliosis in the measurements of spinal deformity , the lordosis in the sagittal plane , pain and quality of life. Attended by 13 individuals who underwent on average 27 ± 15.1 sessions. As the flexion of the spine as compared to the 1st and 2nd evaluation were significant (p = 0.01 ) . There was a decrease in spinal deformity , lumbar lordosis flow , the pain and mobility of the spine and improving quality of life.

O estudo analisou a influência de um programa de exercício em grupo em indivíduos com escoliose idiopática nas mensurações da gibosidade, das lordoses no plano sagital, da dor e da qualidade de vida. Participaram 13 indivíduos que realizaram em média 27±15,1 sessões. Apenas a flexão anterior, da coluna vertebral, quando comparadas a 1ª e 2ª avaliação foram significativas (p=0,01). Houve diminuição da gibosidade, da lordose lombar caudal, da dor, e melhora da mobilidade da coluna e na qualidade de vida.
Keywords: Scoliosis; Exercise; Lordosis; Escoliose; Exercício; Lordose